Massage therapy for the treatment of attention deficit/hyperactivity disorder (ADHD) in children and adolescents: A systematic review and meta-analysis. (February 2019) - Chen, Shu-Cheng; Yu, Branda Yee-Man; Suen, Lorna Kwai-Ping; Yu, Juan; Ho, Fiona Yan-Yee; Yang, Jun-Jun; Yeung, Wing-Fai
Highlights: The use of complementary and alternative medicine for childhood attention and hyperactivity problems is common. Massage therapy seems to be beneficial for ADHD, but there has been no systematic review to summarize the evidence before. Individual studies suggested that massage therapy was superior to exercise, relaxation therapy, and waitlist control. A meta-analysis of the 4 RCTs seemingly suggested that Tuina was better than methylphenidate in improving ADHD symptoms. Abstract: Objective: To summarize the current evidence on the effects and safety of massage therapy for the treatment of ADHD in children and adolescents. Method: A systematic review of 8 randomized controlled trials (RCTs) and 3 case series studies was conducted with a meta-analysis of 4 of the RCTs. Results: Pooled analysis showed that massage produced more improvement in ADHD symptoms in terms of effective rate compared to Ritalin (risk ratio: 1.39, 95%CI: 1.16 – 1.66; P = 0.0004). Individual RCTs suggested that massage was differed significantly from waitlist control in improving the conditions of anxious–passive (mean difference: −11.7; 95%CI [−17.84, −5.56]; P = 0.0002), and asocial behavior (mean difference = − 8.60; 95%CI [−15.87, −1.33]; P = 0.02). Conclusion: Evidence suggests that massage therapy is beneficial for treating ADHD in children and adolescents.